PENGARUH LESSON STUDY TERHADAP KETERAMPILAN MENULIS RPP GURU-GURU SEKOLAH DASAR - Rohana Rohana; Musnar Indra Daulay; Ramdhan Witarsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Lesson study is rarely implemented in primary schools. Primary school teachers' lesson plan writing skills are still diverse and not well standardised, which is one of the problems behind this research. Lesson study can also be conducted at the primary school level. This research aims to measure the effect of lesson study on primary school teachers' lesson plan writing skills. The method used in this research is quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting the research problem, developing research hypothesis, creating research design, conducting pretest, conducting experiment, conducting posttest, processing and analysing data, and drawing conclusion. The research sample was six teachers, consisting of three teachers in the experimental group and three teachers in the control group. The data collection technique used was the assessment of lesson plan documents that teachers had previously made. The results showed that lesson study had a significant effect on the lesson plan writing skills of primary school teachers in group A/experiment. Teachers should be encouraged to continue to improve their lesson plan writing skills so that the lesson plan can be used by other teachers if the teacher is absent. Lesson study research can be continued by further researchers in terms of measuring the suitability between lesson plans that have been made and their implementation in the classroom.